O związkach pamięci zbiorowej i polityki zagranicznej. Jad wa-Szem jako przykład wykorzystania traumy Zagłady w dyskursie dotyczącym konfliktu izraelsko-palestyńskiego - Golańska, Dorota (Historia i Polityka, 2020)
Adopting a new materialist perspective, the article analyzes the exhibition offered by the historical museum of Yad Vashem in Jerusalem to commemorate Shoah. It aims at exposing the subtle references the exhibition makes to the Israeli-Palestinian conflict. The argumentation reveals the multiple ways in which official strategies of remembering the traumatic past are shaped by contemporary discourses or political challenges, placing emphasis on the important intersections of historical policy and current political ventures.